ANALISIS KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus Kabupaten Pasaman) - Martina Martina; Tartila Devy (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to determine the analysis of the contribution of advertising tax in increasing the original regional income of Pasaman district. This type of research is descriptive qualitative research. This research was conducted at the Regional Financial Agency of Pasaman district. The type of data used is quantitative data which will then be analyzed using qualitative analysis. This data collection technique is in the form of primary data, namely data taken from interviews. As well as secondary data in the form of budget realization report data for 2019-2023. The results of this research show that the contribution of advertising tax to the original regional income of Pasaman Regency in 2019-2023 is at a percentage of 0% -10% which is classified as contributing very little to the original regional income. Eflorts to increase advertising tax receipts towards Pasaman Regency's original regional income by conducting outreach to the community, especially to business actors about the importance of paying advertising tax in accordance with applicable regulations, the government, especially the Regional Financial Agency, is also carrying out activities to control and organize illegal billboards in collaboration with Satpol PP to check problematic conditions, provide strict sanctions in the form of fines that violate the provisions of advertisement tax regulations, supervise the installation of advertisements that do not have permits or have not paid taxes, and provide services to taxpayers, both in terms of registration, consultation and payment tax.